Verwaltungsrecht in der Klausur - Eisentraut, Nikolas (De Gruyter Studium, 2020)
This is the first textbook to present open access materials in administrative law geared toward the test-taking realities of law students. Focused on administrative process, it deftly presents the main areas of general administrative law, the specific topics covered by the tests, and detailed case examples.